Antileishmanial Activity of Flavones-Rich Fraction From Arrabidaea chica Verlot (Bignoniaceae) - Silva-Silva, João Victor; Moragas-Tellis, Carla Junqueira; Chagas, Maria do Socorro dos Santos; Souza, Paulo Victor Ramos de; Souza, Celeste da Silva Freitas de; Hardoim, Daiana de Jesus; Taniwaki, Noemi Nosomi; Moreira, Davyson de Lima; Dutra Behrens, Maria; Calabrese, Kátia da Silva; Almeida-Souza, Fernando (Frontiers in Pharmacology, 2021)
With the challenge of identifying new compounds for the treatment of leishmaniasis, this study aimed to evaluate, from in vivo trials, the activity of flavones from Arrabidaea chica against Leishmania amazonensis. The chromatographic profiles of the hydroethanolic extract and a flavone-rich fraction (ACFF) from A. chica were determined by High-Performance Liquid Chromatography coupled with a Diode-Array UV-Vis Detector (HPLC-DAD-UV) and electrospray ionization mass spectrometry in tandem (LC-ESI-MS-MS). The flavones luteolin (1) and apigenin (2), isolated from chromatographic techniques and identified by Nuclear Magnetic Resonance of 1H and 13C, were also quantified in ACFF, showing 190.7 mg/g and apigenin 12.4 mg/g, respectively. The other flavones were identified from the comparison of their spectroscopic data to those of the literature. The in vitro activity was assayed against promastigotes and intramacrophagic amastigote forms of L. amazonensis. Cytotoxicity tests were performed with peritoneal macrophages of BALB/c mice. Nitrite quantification was performed with Griess reagent. Ultrastructural investigations were obtained by transmission electron microscopy. Anti-Leishmania assays indicated that the IC50 values for ACFF, apigenin, and luteolin were obtained at 40.42 ± 0.10, 45.60 ± 1.08, and 31.51 ± 1.13 μg/mL against promastigotes, respectively. ACFF and flavones displayed a concentration-dependent cytotoxic. ACFF and luteolin also inhibited the intra-macrophagic parasite (IC50 3.575 ± 1.13 and 11.78 ± 1.24 μg/mL, respectively), with a selectivity index of 11.44 for ACFF. Promastigotes exposed to ACFF and luteolin exhibited ultrastructural changes, such as intense cytoplasm vacuolization and mitochondrial swelling. These data evidence the antileishmanial action of flavone-rich fractions of A. chica against L. amazonensis, encouraging further studies.